Efeito de parâmetros variáveis de fermentação sobre o crescimento celular e composição química do fermentado de batata-doce - Bringhenti, Lizandra [UNESP]; Cabello, Claudio [UNESP] (EIA Energy in Agriculture, 2010)
This study aimed to evaluate the use of sweet potato as a substrate for the production of spirits. In order to promote an alternative technologically feasible, an experimental design was performed to minimize the operations of preparation, defining the most adequate conditions for the fermentation process. From sweet potato flour obtained by milling and dehydration process of the roots was carried out an enzymatic process of hydrolysis-saccharification of suspension of sweet potato flour with 18% dry matter. The hydrolyzate was used in the fermentation process which followed the 23 full factorial experimental design with central and axial points, and the independent variables were the concentration of reducing sugars, concentration of viable yeast and fermentation temperature. The dependent variables were viable cells, residual sugar, ethanol, glycerol and methanol. The dependent variables were quantified by liquid chromatography. The data analysis indicate that the best fermentation conditions among the tested conditions were: concentration of yeast 5 x 107-1 x 108 in number of viable cells, total reducing sugars from 12.5 to 13.5% and temperature between 33 -34ºC.

Este trabalho teve por objetivo avaliar o uso da batata-doce como substrato para a produção de bebida destilada. No sentido de promover uma alternativa tecnologicamente viável, traçou-se um planejamento experimental que minimizasse as operações de preparo, definindo as condições mais adequadas para o processo fermentativo. A partir da farinha de batata doce obtida por processo de desidratação e moagem das raízes foi realizado um processo enzimático de hidrólise-sacarificação de suspensão da farinha de batata-doce com 18% de matéria seca. O hidrolisado obtido foi utilizado no processo fermentativo que seguiu o planejamento experimental fatorial completo 23 com pontos centrais e axiais, sendo as variáveis independentes a concentração de açúcares redutores, concentração de leveduras viáveis e temperatura da fermentação. As variáveis dependentes foram células viáveis, açúcares residuais, etanol, glicerol e metanol. As variáveis dependentes foram quantificadas por cromatografia líquida. A análise dos dados permitiu indicar que as melhores condições de fermentação dentre as condições testadas foram: concentração de leveduras 5 X 107 - 1 x 108 em número de células viáveis, açúcares redutores totais de 12,5 - 13,5 % e temperatura entre 33 - 340C.
Effect of variables fermentation parameters on celular growth and chemical composition of sweet potato fermented
Keywords: Alcohol; Starchy; Fermentation; Álcool; Amiláceo; Fermentação